ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) DAN RETURN ON ASSETS (ROA) PADA PT. INDOCEMENT TUNGGAL PRAKARSA TBK - Danna, Sulfiani Elfreda (EKONOMIA, 2020)
Sulfiani : Analysis of financial performance using the method of Economic Value Added (EVA) and Return On Assets (ROA) at PT. Indocement Tunggal Prakarsa Tbk (under the guidance of Mrs. Elfreda Aplonia Lau as mentor I and Mrs. Danna Solihin as mentors II). The purpose of this study is to analyze and study the growth of financial performance of PT. Indocement Tunggal Prakarsa Tbk with the method of Economic Value Added (EVA) and Return On Assets (ROA) in the period 2013-2017. The theoretical basis used in this study is financial management that focuses on the methods of Economic Value Added (EVA) and Return On Assets (ROA). Kasmir (2010: 5) explains that